Zinc-doped Prussian blue enhances photothermal clearance of Staphylococcus aureus and promotes tissue repair in infected wounds - Jun Li (Nature Portfolio, 2019)
Here, the authors apply transition metal doping in combination with phototermal therapy to treat Staphylococcus aureus-infected wounds, and show that release of ions by local heat enhances bacteria clearance and promotes tissue repair in a rat model of MRSA-infected wounds